Clinical Outcome after Intra-Arterial Stroke Therapy in the Very Elderly: Why is it so Heterogeneous? - Chandra, Ronil V.; Leslie-Mazwi, Thabele M.; Mehta, Brijesh P.; Yoo, Albert J.; Simonsen, Claus Z. (Frontiers in Neurology, 2014)
Very elderly patients (i.e. ≥80 years) are disproportionally affected by acute ischemic stroke. They account for a third of hospital stroke admissions, but two thirds of overall stroke-related morbidity and mortality. There is some evidence of clinical benefit in treating selected very elderly patients with intravenous thrombolytic therapy (IVT). For very elderly patients ineligible or non-responsive to IVT, intra-arterial therapy (IAT) may have promise in improving clinical outcome. However, its unequivocal efficacy in the general population remains to be proven in randomized trials. Small cohort studies reveal that the rate of good clinical outcome for very elderly patients after IAT is highly variable, ranging from 2% to 28%. In addition, they experience higher rates of futile reperfusion than younger patients. Thus it is imperative to understand the factors that impact on clinical outcome in very elderly patients after IAT. The aim of this review is to examine the factors that may be responsible for the heterogeneous clinical response of the very elderly to IAT. This will allow the reader to integrate the current available evidence to individualize intra-arterial stroke therapy in very elderly patients. Placing emphasis on pre-stroke independent living, smaller infarct core size, short procedure times, and avoiding general anesthesia where feasible, will help improve rates of good clinical outcome.